Local involvement of the optic nerve by acute lymphoblastic leukemia - Bernardczyk-Meller, Jadwiga; Stefańska, Katarzyna (Klinika Oczna / Acta Ophthalmologica Polonica, 2005)
The leucemias quite commonly involve the eyes and adnexa. In some cases it causes visual complaints. Both, the anterior chamber of the eye and the posterior portion of the globe may be sites of acute or chronic leukemia and leucemic relapse. We report an unique case of a 14 years old leucemic patient who suffered of visual loss and papilloedema, due to a unilateral local involvement within optic nerve, during second relapse of acute lymphocytic leucemia. In spite of typical treatment of main disease, the boy had died. The authors present typical ophthalmic features of the leucemia, too.